Words Threatened with Insignificance. Critique and Testimony in Oración, by María Moreno (2018): Crítica y testimonio en Oración, de María Moreno (2018) (El Taco en la Brea, 2025)
This essay proposes a reading of Oración (2018), by María Moreno, focusing on the ways in which the book intervenes on the theory and practice of testimony, an object that, in the context of the Argentine post‒dictatorship, has come to occupy a relevant place in literary production and critical discourse. We will be interested in reading Oración as a point of arrival of the intense debates raised by testimony in the post‒dictatorship period, and as a starting point to update those debates in the present, in a context in which the struggle for the past, as Elizabeth Jelin puts it, is repositioned at the center of public debate. Moreno's book brings into play, on the one hand, a theory of the testimonial that seeks to problematize the status of these narratives, and, on the other, deploys a writing practice in which the reverberations of testimony do not cease to insist. In the tensions that emerge between the uses of testimony and the interrogation of the problems it raises, lie the originality of the book and its potential for critical reflection.
Keywords: testimony; critique; literature; fiction; post‒dictatorship